Gelatinase B/matrix metalloproteinase-9 is a phase-specific effector molecule, independent from Fas, in experimental autoimmune encephalomyelitis. - Estefania Ugarte-Berzal; Nele Berghmans; Lise Boon; Erik Martens; Jennifer Vandooren; Bénédicte Cauwe; Greet Thijs; Paul Proost; Jo Van Damme; Ghislain Opdenakker (PLoS ONE, 2018)
Gelatinase B/matrix metalloproteinase-9 (MMP-9) triggers multiple sclerosis (MS) and the animal model of experimental autoimmune encephalomyelitis (EAE) by the breakdown of the blood-brain barrier. Interestingly, MMP-9 is beneficial in systemic autoimmunity caused by Fas-deficiency. Fas-deficient (faslpr) and Fas-ligand-deficient mice are protected against EAE. We here investigated the interaction between Fas and MMP-9 in the setting of induction of EAE and compared short- and long-term effects. We provoked EAE with myelin oligodendrocyte glycoprotein (MOG) peptide and compared EAE development in four genotypes (wild-type (WT), single knockout mmp-9-/-, faslpr, and mmp-9-/-/faslpr) and monitored leukocytes, cytokines and chemokines as immunological parameters. As expected, faslpr mice were resistant against EAE induction, whereas MMP-9 single knockout mice were not. In the double mmp-9-/-/ faslpr mice the effects on disease scores pointed to independent rather than interrelated disease mechanisms. On a short term, after EAE induction leukocytes infiltrated into the brain and cytokine and chemokine levels were significantly higher in all the four genotypes studied, even in the faslpr and mmp-9-/-/faslpr, which did not develop clinical disease. The levels of MMP-9 but not of MMP-2 were increased in the brain and in the peripheral organs after EAE induction. After 40 days all the animals recovered and did not show signs of EAE. However, the absence of MMP-9 in the remission phase suggested a protective role of MMP-9 in the late phase of the disease, because single mmp-9-/- mice presented a delayed remission in comparison with WT animals suggesting a phase-dependent role of MMP-9 in the disease. Nevertheless, the levels of some cytokines and chemokines remained higher than in control animals even 100 days after EAE induction, attesting to a prolonged state of immune activation. We thus yielded new insights and useful markers to monitor this activated immune status. Furthermore, MMP-9 but not MMP-2 levels remained increased in the brains and, to a higher extend, in the spleens of the WT mice even during the remission phase, which is in line with the role of MMP-9 as a useful marker and a protective factor for EAE in the remission phase.